(untitled) (TERRA LATINOAMERICANA, 2025)
Irrigation District 025, located in northeastern Mexico, faces adverse climatic conditions characterized by a dry climate and insufficient rainfall for optimal agricultural development. This situation has been exacerbated by Climate Change (CC), which has significantly reduced agricultural yields. Our study, classified as empirical with an associative strategy, aimed to evaluate the economic impact of water stress on agricultural production using three key indicators: the Economic Value of the Water Footprint (HHvalor), Irrigation Supply Efficiency (ESRhh), and Agricultural Production Value (Vp). The non-experimental methodology included the analysis of water footprints, water productivity, current irrigation conditions, and agricultural and hydrometric statistics, associated with two scenarios: an ideal scenario without water stress (Baseline, LB) and a scenario with water stress (Real Condition, RC). Meteorological data were generated using WXGEN and processed with FAO’s CROPWAT 8.0 software to calculate irrigation requirements for the main crops. The results showed that the highest economic impact of water stress was obtained with HHvalor ( 798 110 647.64), followed by ESRhh ( 215 410 806.25) and Vp ( 72 341 989.32), with an average impact of 361 223 351.00. The main limitations of the study included the lack of directly measured meteorological and physiological data for the crops. Nevertheless, the developed indicators and methodology provide effective tools to quantify and mitigate economic losses resulting from water stress, contributing to more efficient water management in agriculture. In conclusion, our main finding was that HHvalor allows for a comprehensive assessment of the economic impact of water stress on irrigated agricultural production, as it incorporates both the water footprints of crops and their intrinsic economic value.